Pengaruh Disiplin, Kompetensi dan Lingkungan Kerja terhadap Kinerja Pegawai di Sekretariat Kabupaten Aceh Barat Daya - Eliza Ariesta (Jurnal Ekonomi Manajemen Akuntansi, 2024)
This study aims to analyze the influence of discipline, competence, and work environment on employee performance at the Southwest Aceh Regency Secretariat. The method used is quantitative with a survey approach. Data was collected through a questionnaire using the Likert scale and involved 30 respondents who were secretariat employees. Data analysis was carried out using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The results of the study show that discipline, competence, and work environment have a positive effect on employee performance. The reliability test of the instrument showed a Composite Reliability value of more than 0.7, which indicates that the research instrument has a good level of internal consistency. These findings show that improving discipline, competence, and a conducive work environment can improve employee performance at the Southwest Aceh Regency Secretariat. This research has implications for local governments in designing policies that focus on improving work discipline, developing employee competencies, and creating a more productive work environment to increase organizational work effectiveness.